Analisis Kelayakan Budidaya Ikan Nila dengan Sistem Akuaponik dan Pakan Buatan di Dusun Ponggang, Jawa Barat - Siantara, Adriel Pradita; Limantara, Lydia; Dewi, Lucyana (Metris: Jurnal Sains dan Teknologi, 2017)
Fish is an alternative to animal protein to meet the needs of various circles of society. This is evidenced by the contribution of fish proteins to animal protein consumption reaches 57% of Indonesian society. With the increasing demand for fish consumption in the community, then it needs to be made of fish farming as a source of fish supply. Tilapia fish (nila fish) is one commodity that can be developed for the domestic market and export. The problem that often arises is about the feasibility of fish farming itself, the lack of quality water to the source of fish life, and high costs necessary for the fulfillment of fish feed on a system of fish farming, because in general the price of fish food available in the market are relatively expensive. In this research, feasibility analysis tilapia fish farming with artificial feed is integrated with Aquaponics system in Ponggang Village, West Java. This research was conducted in the Ponggang Village, district Serang Panjang, Subang, West Java, namely to develop activities in fish farming to make fish feed artificial raw materials are easily obtained by the local community and with simple techniques, so the approach taken more towards rural communities, namely that the local community is able to apply and costs need to be incurred for the preparation of an integrated system of fish farming is also relatively small.